Representation of Sharenting in Rans Entertainment YouTube Content: (Semiotics Analysis of “Banjir Undangan TV!! Raffi Nagita Support Bakat Cipung di Dunia Entertainment, Cipung Anteng Aja.”) - Amira Balqis Sandika; Swita Amallia Hapsari (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
Sharenting or a phenomenon in which parents share their kids’ daily life has become a current trend in social media websites such as YouTube. This trend has also become famous in Indonesia since two Indonesian public figures, Raffi Ahmad and Nagita Slavina regularly share their sharenting contents on their Rans Entertainment YouTube channel. The researcher aimed to examine one of the sharenting contents of Rans Entertainment sharenting titled